Prawo pacjenta do dostępu do elektronicznej dokumentacji medycznej - Klimas, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article is devoted to the issue of electronic medical records as a progressive instrument of implementation the patient’s right to information. Reason for such analysis is an obligation of archiving medical records only in electronic form in force since 1 January 2018 as well as possibility to share documentation in the Polish Medical Information System planned from 1 August 2017. Therefore there is a fundamental change in the form in which the patient will obtain access to the records and perform his information rights.In following considerations, the author will peform evaluation of expected law modifications, starting with explanation of the term „electronic medical records” and marking the historical background of development in this range. In the further part, will be presented the advantages of processing electronic.
Keywords: electronic medical records; right to information; information in healthcare; Polish Medical Information System; patient’s rights; medical law